2021
DOI: 10.1002/jmv.26887
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of viral metagenome from cancer tissue and blood from patients with lung adenocarcinoma

Abstract: In this study, using a viral metagenomic method, we investigated the composition of virome in blood and cancer tissue samples that were collected from 25 patients with lung adenocarcinoma. Results indicated that virus sequences showing similarity to human pegivirus (HPgV), anellovirus, human endogenous retrovirus (HERV), and polyomavirus were recovered from this cohort. Three different complete genomes of HPgV were acquired from the blood samples and one complete genome of polyomavirus was determined from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Recent studies have indicated that global virome signatures may serve as markers of cancer development. Viral metagenomic signatures have been detected in lung adenocarcinoma biopsies (Cai et al, 2021) and more than 100 tumor samples, including oral, breast, colon, and genitourinary cancers (Mollerup et al, 2019). Cantalupo et al suggested that HPV, a known cause of cervical cancer and potentially other genitourinary cancers, is additionally correlated with tumor progression in head and neck cancers as well as bladder cancers (Cantalupo et al, 2018;IARC, 2009).…”
Section: Nonbacterial Cancer-associated Microbesmentioning
confidence: 99%
“…Recent studies have indicated that global virome signatures may serve as markers of cancer development. Viral metagenomic signatures have been detected in lung adenocarcinoma biopsies (Cai et al, 2021) and more than 100 tumor samples, including oral, breast, colon, and genitourinary cancers (Mollerup et al, 2019). Cantalupo et al suggested that HPV, a known cause of cervical cancer and potentially other genitourinary cancers, is additionally correlated with tumor progression in head and neck cancers as well as bladder cancers (Cantalupo et al, 2018;IARC, 2009).…”
Section: Nonbacterial Cancer-associated Microbesmentioning
confidence: 99%
“…Metagenomic analysis of the virome in the blood and nonsmall cell lung cancer tissues has revealed an abundant HERV presence 68 . Significantly increased levels of HERV‐K, HERV‐H, HERV‐P, and HERV‐R env mRNAs have been recognized in lung cancer tissues compared to healthy controls 69 .…”
Section: Herv Participation In Malignancies and Clinical Implicationsmentioning
confidence: 99%
“…Metagenomic analysis of the virome in the blood and nonsmall cell lung cancer tissues has revealed an abundant HERV presence. 68 Significantly increased levels of HERV‐K, HERV‐H, HERV‐P, and HERV‐R env mRNAs have been recognized in lung cancer tissues compared to healthy controls. 69 Adenocarcinoma tissues demonstrated the most prominent increases compared to other lung cancer histological types, and HERV‐K, HERV‐H, and HERV‐P levels were distinctive for lung adenocarcinoma compared to squamous and small‐cell lung cancer.…”
Section: Herv Participation In Malignancies and Clinical Implicationsmentioning
confidence: 99%
“…This observation makes the scenario of a potential role of ERVs in human cancer plausible, as this is a rare form of the disease, lacking the usual exposures of this malignancy. Furthermore, metagenomic analyses in the virome of lung cancer tissues and blood from lung adenocarcinoma revealed the presence of multiple HERV families (216).…”
Section: Hervs and Human Cancer: Link Therapeutic And Prognostic Perspectivesmentioning
confidence: 99%